find ∠AEC in the figure below.

Answer:
C. 105°
Step-by-step explanation:
Angles BED and CED are supplementary, so ...
(2y +x) +(-2y +3x) = 180
4x = 180
2x = 90
Substituting this into the expression for angle AEB, we have ...
Angle AEB = (90 -15)° = 75°
Angle AEC is the supplement to that, so is ...
∠AEC = 180° -75° = 105° . . . . . matches choice C
Answer: C. 105
Step-by-step explanation:
Adding BED and DEC for being adjacent angles we obtain:
[tex]2y+x +-2y+3x = 180\\4x = 180\\x=45\\[/tex]
Substituting x in BEA
[tex]BEA=2(45)-15=75[/tex]
Adding BEA and AEC for being adjacent angles we obtain:
[tex]BEA+AEC=180\\AEC=180-BEA\\AEC=180-75\\AEC=105[/tex]